Recent advances in bio-medical implants; mechanical properties, surface modifications and applications - Zwawi, Mohammed (Engineering Research Express, 2022)
The demand for bio-medical implants has significantly increased to treat different medical conditions and complications. The latest research in medical and material science is paving the path for the new generation of biomedical implants that mimic the natural bone and tissues for enhanced biocompatibility. A bio-medical implant must be bio-compatible, non-toxic and bioactive. The main reasons for implantation are ageing, overweight, accidents and genetic diseases such as arthritis or joint pain. Diseases such as osteoporosis and osteoarthritis can severely damage the mechanical properties of bones over time. Different materials including polymers, ceramics and metals are used for biomedical implants. Metallic implants have high strength and high resistance to corrosion and wear. Biocompatible metallic materials include Ti, Ta, Zr, Mo, Nb, W and Au while materials such as Ni, V, Al and Cr are considered toxic and hazardous to the body. Bioresorbable and degradable materials dissolve in the body after the healing process. Mg-based metallic alloys are highly degradable in the biological environment. Similarly, different polymers such as Poly-lactic acid (PLA) are used as bio-degradable implants and in tissue engineering. Biodegradable stents are used for the slow release of drugs to avoid blood clotting and other complications. Shape memory alloys are employed for bio-implants due to their unique set of properties. Different surface physical and chemical modification methods are used to improve the interfacial properties and interaction of implant materials with the biological environment. This review explains the properties, materials, modifications and shortcomings of bio-implants.